The Impact of Consumer Price Index, Foreign Direct Investment, Bank Credit and Labour Force on Economic Growth in Indonesia (Business and Economic Analysis Journal, 2021)
This study aims to analyse the impact of consumer price index on GDP, to analyse the im-pact of Foreign Direct Investment (FDI) on GDP, to analyse the impact of bank credit on GDP, to analyse the impact of Labour Force on GDP. The sample in this study are the data for GDP, direct investment (FDI), bank credit, Consumer Price Index, and the labour force with annual data for fourteen consecutive years that are from period 2005-2019 years. ECM with e-views programs used to analyse the data. Based on the results of data analysis and discussion that has been presented, the following conclusions can be drawn that Con-sumer Price Index (CPI) has no impact on GDP in short term and long term, Foreign Direct Investment (FDI) has an impact on GDP in short term and long term, Bank Credit (BC) has no impact on GDP in short term and long term, Labour Force (LB) has no impact on GDP in short term and long term.